PENGEMBANGAN SISTEM INFORMASI APLIKASI PETA BANDARA BERBASIS WEBSITE UNTUK MENINGKATKAN PELAYANAN PENGGUNA JASA DI BANDARA INTERNASIONAL JUANDA SURABAYA - Afilda Bidayatur Rahmah; Ariyono Setiawan; Totok Warsito (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
The development of website-based airport map information system aims to improve services for customer. Hopefully, with the presence of this website-based airport map application information system will support the improvement of services for customers at Juanda International Airport. The data that will be used in this information system is the map of terminal 1 and 2 Juanda Airport and check in informations of every airlines. The next stage of designing, the researcher used planning tool in form of flow diagram by using flowchart and unified language system (UML) and developed by using Software Content Management System (CMS). The method that used in this research is Research and Development (R&D), with the pocedure of model development analysis, design, development, implementation, and evaluation (ADDIE). The development of airport map application information system has been tested on several online customers and can be used to improve services for customers while searching locations at Juanda Airport Surabaya.